TINJAUAN FILOSOFIS BUDAYA AGRARIS RERESIK LAK - Reni Dikawati (Balai Pelestarian Nilai budaya Daerah Istimewa Yogyakarta, 2019)
Reresik Lak illustrates how agrarian culture is performed by the community of Ngiring village through water conservation practices. The narrative of Air Lak in the system mentality of Ngiring community is related to the belief in the existence of water as the main source of life (macrocosm). The focus of this research is to examine Reresik Lak as a cultural reproduction and as an agrarian ritual of the existence of water resources. The results showed that genealogically the development of Reresik Lak is not merely a form of a reproduction of Javanese agrarian culture. It also relates to the mentality system of the society. The philosophical values of religiosity and agrarian have been internalized as ethics and wisdom of life. The significance of this research is because water conservation is an important factor that supports agriculture of the people. Dissemination of the idea of water conservation will support agricultural development. Water conservation practice which is initialized in villages will contribute the economy of Indonesian people. The philosophical values of the Reresik Lak will build awareness of the importance of preserving noble values as a wisdom of life.The implication of the ritual Reresik Lak is not only an effort to conserve nature, but also to encourage the realization of cultural identity that eventually strengthens nationalism.